PENGARUH FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPEMPENGARUHI PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH DI INDONESIA - Firdaus, Rizal Nur (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
This study aims to answer some questions about the factors that influence theoccurrence of non-performing finanncing at sharia banks in Indonesia. Hypothesistesting is performed by multiple linear regression analysis to determine theeffect of the internal variables (Growth Capital Financing and adequencyRatio) and external variables (Gross Domestic Product, Inflation and ExchangeRate) on the occurrence of non-performing Finanncing (NPF) in Islamic banksin Indonesia. Sources of data in this study came from Bank Indonesia BankIndonesia website. Period examined data starts from March 2008 to December2012 with a 3-month data collection. The study shows that simultaneous eachfactor in the internal and external variables have a significant influence onthe occurrence of NPF at the 5% significance level. But partially, financingvariables, inflation and the exchange rate has no significant effect on theoccurrence of NPF while CAR and GDP variables have a significant influence.